Prescription Monitoring Study of Antipsychotic Drugs in Geriatric Population at Tertiary Level Referral Hospital in Rural India - C, Dilip.; K.M.K, Dinesh; R, Divya; M.M, Lisa (Indian Journal of Pharmacy Practice)
An attempt was made to assess the prescription monitoring pattern of anti-Psychotic drugs in geriatric patients treated at tertiary level referral hospital and to rationalise the prescription habits of the clinicians. The study was conducted in tertiary level multispecialty referral hospital at Perinthalmanna. It was a prospective and observational study conducted among inpatients for four weeks by monitoring the case sheets and patient interview in the hospital. The study was conducted to systematically assess the prescribing patterns of antipsychotic drugs among geriatric inpatients. A total of 65 geriatric patients were admitted to the hospital during the study period. . The indicator-driven analysis of antipsychotic prescribing quality revealed a need for improvement, with the main prescribing problems relating to duration and combination of therapies.